(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It has become very relevant in today’s competitive environment to figure out what defines an employee’s professional performance in an organization. An significant aspect that can help in assessing employee performance is emotional intelligence (EI). Numerous studies have shown empirically that EI has a profound influence on an employee’s organizational existence. Emotional intelligence can be the key for human resource managers and organizations, especially in service organizations, as organizations strive to find different ways to achieve competitive advantage by promoting employee innovation, getting best results from their workers, retaining talented employees and ultimately organizational effectiveness. There is not much research related to the role of emotional intelligence in the workplace, especially in the North-East area. This study seeks to determine whether emotional intelligence has a role to play in employee’s success at workplace, organizational engagement and ethical understanding of employees.